2013
DOI: 10.1371/journal.pone.0053222
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell and Population NF-κB Dynamic Responses Depend on Lipopolysaccharide Preparation

Abstract: BackgroundLipopolysaccharide (LPS), found in the outer membrane of gram-negative bacteria, elicits a strong response from the transcription factor family Nuclear factor (NF)-κB via Toll-like receptor (TLR) 4. The cellular response to lipopolysaccharide varies depending on the source and preparation of the ligand, however. Our goal was to compare single-cell NF-κB dynamics across multiple sources and concentrations of LPS.Methodology/Principal FindingsUsing live-cell fluorescence microscopy, we determined the N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 24 publications
2
24
0
Order By: Relevance
“…Different types of LPS have been shown to produce dramatically different host responses, with diversity in LPS structures having been described between bacterial populations exposed to different environments (Paciello et al, 2013), different bacterial mutants (Guo et al, 1997), and different LPS variants resulting from different isolation procedures (Gutschow et al, 2013). We now show that heterogeneity also exists within a single population of wild-type bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Different types of LPS have been shown to produce dramatically different host responses, with diversity in LPS structures having been described between bacterial populations exposed to different environments (Paciello et al, 2013), different bacterial mutants (Guo et al, 1997), and different LPS variants resulting from different isolation procedures (Gutschow et al, 2013). We now show that heterogeneity also exists within a single population of wild-type bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…7). It will be interesting in the future to examine which features of the signaling dynamics are shared across different sources of LPS (32) and other TLR ligands. Analog information processing and feedback dominance switching may also be important in other cell types that require accurate single-cell-level decision-making to mount functional responses to specific signals.…”
Section: Discussionmentioning
confidence: 99%
“…Hao and Baltimore found that TNFα mRNA degradation is several-fold lower when TNFα is produced in response to LPS when compared to TNFα stimulation [67]. This explains why the LPS stimulation leads to the massive secretion of TNFα, which in turn may trigger autocrine signaling, leading to prolonged oscillations of NF-κB, observed recently in a fraction of LPS-stimulated cells [68].…”
Section: Introductionmentioning
confidence: 87%